Intravenous ondansetron reduced nausea but not pruritus following intrathecal morphine in children: Interim results of a randomized, double‐blinded, placebo‐control trial. Issue 10 (12th July 2022) - Putnam, Elizabeth M.; Hong, Rebecca A.; Park, John M.; Li, Ying; Leis, Aleda; Malviya, Shobha
Abstract: Study Objective: This study's purpose was to determine if ondansetron can prevent pruritus after administration of intrathecal morphine in children, as has been demonstrated in adults. Design: A double‐blinded, randomized placebo‐controlled trial. Setting: Operating room and first 24 h postoperative inpatient stay at an academic children's hospital. Patients: Forty‐six children aged 3–17 years, who received 4–5 mcg/kg intrathecal morphine for urological or orthopedic procedures were included. Interventions: Children were randomized to receive intravenous ondansetron (treatment) or saline placebo (placebo), prior to intrathecal morphine administration, and q6H for 24 h thereafter. Intraoperative anti‐emetics and postoperative rescue treatments for pruritus and nausea were standardized. Measurements: Patients were interviewed q6H for scored pruritus, nausea, and pain, using standardized scales. Main Results: The trial was terminated for futility after interim analysis. Forty‐six children were recruited and 45 completed data collection. No significant difference was found between both groups for incidence of pruritus (requiring treatment) [relative risk (RR) 0.9, 95% CI: 0.7, 1.2], during the first postoperative 24 h. Notably, the incidence of pruritus was 84% overall, much higher than rates in previously published studies. Intravenous ondansetron significantly reduced the incidence of nausea, compared with the placebo group [RR 0.5, 95% CI: 0.3, 0.9]. Conclusions: This study found no evidence for intravenous ondansetron as an effective preventative for pruritus following intrathecal morphine in children. However, this RCT did find that the rate of pruritus following intrathecal morphine administration may be significantly higher than previously thought. Nausea and vomiting (a secondary outcome) were reduced significantly in the treatment group. The negative findings of this study reinforce the potential dangers of extrapolating the drug effects seen in adults onto pediatric patients.